Duplex stainless steel containing rare earth elements and preparation process of duplex stainless steel
By adding rare earth elements to duplex stainless steel and controlling smelting technology, the problems of side crack defects and low material yield during thermal processing of duplex stainless steel are solved, and its purity, corrosion resistance and thermal processing performance are improved.
Patent Information
- Application Number
- CN202411946153.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
AI Technical Summary
Duplex stainless steel is prone to edge crack defects during hot processing, has a low material yield, and high Cr content affects the thermal processing performance. The increase of N and Mn leads to a decrease in stress corrosion performance.
Duplex stainless steel containing rare earth elements is used to control the components and heat treatment conditions through specific smelting and refining processes, and add trace amounts of mixed rare earths, combined with argon protection and solid solution treatment, and refine grains and inclusions.
The purity, corrosion resistance, thermal processing performance and material yield of duplex stainless steel are significantly improved, and the elongation, impact toughness and corrosion resistance are improved, and the cost is reduced.
Smart Images

Figure CN119663115A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to duplex stainless steel, in particular to duplex stainless steel containing rare earth elements and a preparation process thereof. Background Art
[0002] Duplex stainless steel has a two-phase structure of austenite and ferrite. By properly controlling the chemical composition and heat treatment process, it has the advantages of both ferritic stainless steel and austenitic stainless steel. It has excellent toughness, weldability, high strength and good resistance to chloride stress corrosion, and has a broad application market.
[0003] At present, there are two key problems in special steel: segregation and inclusions. Segregation is mainly manifested in uneven organization and uneven element distribution. Improper control will lead to unqualified flaw detection of forgings or even scrapping. Inclusions will promote the formation of segregation, and large-sized inclusions will seriously affect the performance of the material. Therefore, for duplex stainless steel, inclusion control (control of inclusion morphology, size, and distribution) and low oxygen control are the research focuses in this field.
[0004] Duplex stainless steel has excellent corrosion resistance due to its high Cr content, but the high Cr content seriously increases the precipitation tendency of the intermetallic intermediate phase, which has a negative impact on the hot working performance of the steel.
[0005] Duplex stainless steel can improve the strength and ductility of stainless steel due to the high content of austenite elements N and Mn. However, the increase in N content increases the difference between the strength of the austenite phase and the ferrite phase at high temperature, thereby increasing the tendency of cracks to occur during hot working and deteriorating the hot working performance of steel. In addition, the large amount of Mn added also has a negative impact on corrosion performance.
[0006] In addition, since the hot working temperature range of duplex stainless steel is often in the two-phase region with low thermoplasticity, edge crack defects are very likely to occur during the hot working process, and the yield rate is low. Summary of the invention
[0007] The purpose of the present invention is to provide a duplex stainless steel containing rare earth elements and a preparation process thereof. The present invention has the characteristics of improving the purity, corrosion resistance, hot working performance and yield rate of the duplex stainless steel.
[0008] The technical solution of the present invention is a duplex stainless steel containing rare earth elements, comprising the following components in weight percentage: C < 0.04%, Si: 0.2-0.8%, Mn: 0.8-1.5%, S≤0.005%, P≤0.02%, Cr: 22.0-27.0%, Ni: 5.0-7.0%, Mo: 3.0-4.0%, N: 0.24-0.32%, B: 0.002-0.005%, mixed rare earth: 0.05-0.10%, and the balance is iron and other inevitable impurities.
[0009] In the aforementioned duplex stainless steel containing rare earth elements, the mass percentage of cerium in the mixed rare earth is 58-65%; the mass percentage of lanthanum is 30-34%.
[0010] The above-mentioned method for preparing duplex stainless steel comprises the following steps:
[0011] S1. Metal smelting: pure scrap steel with similar composition is added into an electric arc furnace for smelting, and the molten steel is deoxidized and deslaged to make the oxygen content less than 100ppm to obtain molten metal;
[0012] S2, adding alloy to the molten metal for AOD refining and LF refining to obtain refined molten steel;
[0013] S3. When the composition of the molten steel to be refined is qualified and the oxygen content is below 20ppm, a mixed rare earth with an oxygen content of less than 1000ppm is added to the molten steel in batches to the bottom of the ladle by inserting a barrel, and the amount of the mixed rare earth in each batch is less than 500ppm, and the time interval for adding each batch of mixed rare earth is not less than 1 minute and not more than 3 minutes;
[0014] S4, pouring: argon protection, control the argon flow rate to 5-15m3 / h, control the oxygen concentration near the ladle nozzle to below 10ppm, the pouring flow rate to 20-60kg / s, the pouring superheat to 45-65℃; the cooling rate of the molten steel is less than 10℃ / min, and the cast ingot is obtained;
[0015] S5, rolling: the cast steel ingot is used as raw material, and is subjected to heating, rough rolling, finish rolling, cooling and finishing processes to be rolled into bars with a diameter of 10-65 mm;
[0016] S6. Solution treatment: the solution temperature is 1000℃-1250℃, and the holding time is 0.5-2.0h.
[0017] In the aforementioned preparation method of duplex stainless steel, in step S1, during the molten steel smelting process, the boiling time is maintained at 30-50 minutes and the weak stirring time is maintained at 10-40 minutes, so that the inclusions inside the molten metal float to the surface.
[0018] In the aforementioned method for preparing duplex stainless steel, in step S2, the AOD refining time is 60-120 min, and the LF refining time is 30-60 min.
[0019] In the aforementioned preparation method of duplex stainless steel, in step S2, during AOD refining, 2.0-2.5 kg / ton of aluminum blocks are added to perform deep deoxidation of the molten steel, and then calcium oxide is added to perform desulfurization, so that the O content in the molten steel is less than 20 ppm and the S content is less than 10 ppm.
[0020] In the aforementioned preparation method of duplex stainless steel, in step S2, during LF refining, 0.8-1.5 kg / ton of aluminum powder is added to the slag surface for diffusion deoxidation, 0.1-0.15 kg / ton of aluminum wire / shot is fed to the molten steel for precipitation deoxidation, and calcium oxide and 6%-10% by weight of fluorite are added, and the basicity is controlled to be 5-6 to obtain a refined molten steel with components meeting the requirements.
[0021] In the aforementioned preparation method of duplex stainless steel, in step S3, after the mixed rare earth is added, the molten steel is isolated from air for protection, the weak blowing argon pressure is 0.1-0.2MPa, the instantaneous argon flow rate is 0.5-0.6m3 / h, the bottom blowing Ar gas is weakly stirred in the ladle, and the weak stirring time is 10-20min.
[0022] In the aforementioned method for preparing duplex stainless steel, in step S6, the temperature entering the furnace is not less than 200°C, the heating rate is 100-150°C / h, and after solutionizing, the material is water-cooled at room temperature to reduce to room temperature.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention contains lower Ni and Mo element contents, which can not only significantly reduce the production cost of stainless steel, but also improve its elongation, impact toughness and corrosion resistance by adding a trace amount of mixed rare earth, thereby developing low-cost, cost-effective duplex stainless steel.
[0025] The invention contains a relatively high N content, can improve the stress corrosion resistance, tensile strength and elongation of duplex stainless steel, and further inhibit stress corrosion cracking.
[0026] The invention contains a relatively high Cr content, can reduce the passivation current of steel, is beneficial to the passivation of the metal surface, promotes the rapid growth of the passivation film on the metal surface, can form Cr-containing compounds on the surface of the passivation film, promotes the growth of chromium oxides in the subsurface layer of the passivation film, increases the pitting potential, and improves the corrosion resistance.
[0027] The molybdenum in the composition can form molybdenum-containing compounds on the surface of the passivation film, promoting the enrichment of chromium oxides in the inner passivation film. The nitrogen can further enrich the inner passivation film with molybdenum, improve the stability and density of the passivation film, and improve the corrosion resistance.
[0028] The invention controls the amount and mode of adding rare earth, coordinates the pressure and flow rate of argon gas, the pouring speed, the pouring superheat and the solid solution temperature, so that the two-phase ratio of the steel is controlled at 45%-55%, the rare earth and harmful elements such as S in the molten steel form rare earth oxysulfur compounds with high melting points, avoids the segregation of low melting point sulfides at the phase boundary, and refines the grains and inclusions; and through weak blowing of argon gas, it is ensured that the formed reaction products fully float, reduces the content of harmful gases and impurities in the steel, and significantly improves the purity, corrosion resistance, mechanical properties, hot processing properties and yield rate of duplex stainless steel, so that the grain size of the duplex steel prepared by the invention is above level 9, the A-type inclusion is 0, and the B+C+D-type inclusion is ≤ level 2; the yield strength is greater than 650MPa, the tensile strength is 900MPa, the elongation is greater than 25%, the cross-sectional shrinkage is greater than 45%, the impact energy is ≥100J at a temperature below -46°C, and the hot processing performance is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a trend chart of the open circuit potential of the artificial gap electrode of duplex stainless steel Example 1 in a 70°C dead green liquor simulation solution.
[0030] Figure 2 This is the cyclic voltammetry curve of the artificial gap electrode of duplex stainless steel Example 1 in a 70°C dead green liquor simulation solution.
[0031] Figure 3 It is the corrosion morphology of duplex stainless steel Example 1 after testing (a macro corrosion morphology, a' crevice external corrosion morphology, a" crevice internal corrosion morphology).
[0032] Figure 4 The cyclic voltammograms of duplex stainless steel Example 1 in dead green liquor at different temperatures ((a) 20°C; (b) 40°C; (c) 70°C).
[0033] Figure 5 These are the corrosion morphologies of duplex stainless steel Example 1 after cyclic polarization testing in dead green liquor at different temperatures ((a)(b) 20°C; (c)(d) 40°C; (e)(f) 70°C).
[0034] Figure 6 This is a cyclic polarization curve diagram of the gap electrode in Example 1 in a simulated seawater desalination environment.
[0035] Figure 7 This is a microscopic morphology of crevice corrosion of Example 1 in a simulated seawater desalination environment.
[0036] Figure 8The cyclic voltammetry curves of Example 1 in seawater simulation solutions at different temperatures ((a) 20°C; (b) 40°C; (c) 70°C).
[0037] Fig. 9 These are the corrosion morphologies of Example 1 after cyclic voltammetry testing in a 2-fold seawater simulation solution at 20°C and 70°C ((a)(b) 20°C; (c)(d) 70°C).
[0038] Fig.10 This is a graph showing the effects of CaF2 content and basicity on the average diameter of inclusions. DETAILED DESCRIPTION
[0039] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.
[0040] Example:
[0041] A duplex stainless steel containing rare earth elements: comprising the following components in weight percentage: C < 0.04%, Si: 0.2-0.8%, Mn: 0.8-1.5%, S≤0.005%, P≤0.02%, Cr: 22.0-27.0%, Ni: 5.0-7.0%, Mo: 3.0-4.0%, N: 0.24-0.32%, B: 0.002-0.005%, mixed rare earth: 0.05-0.10%, and the balance is iron and other inevitable impurities.
[0042] The mass percentage of cerium in the mixed rare earth is 58-65%; the mass percentage of lanthanum is 30-34%.
[0043] The preparation process of duplex stainless steel includes the following steps:
[0044] S1. Metal smelting: pure scrap steel with similar composition is added into an electric arc furnace for smelting, and the molten steel is deoxidized and deslaged to make the oxygen content less than 100ppm to obtain molten metal; during the molten steel smelting process, the boiling time is maintained at 30-50min and the weak stirring time is maintained at 10-40min to make the inclusions inside the molten metal float to the surface and improve the purity of the molten metal.
[0045] S2. Add alloy to the molten metal for AOD refining and LF refining. The AOD refining time is 60-120min, and the LF refining time is 30-60min. During AOD refining, add 2.0-2.5kg aluminum blocks / ton of steel for deep deoxidation, and then add calcium oxide for desulfurization, so that the O content in the molten steel is less than 20ppm and the S content is less than 10ppm; during LF refining, add 0.8-1.5kg aluminum powder / ton of steel for diffusion deoxidation, and feed 0.1-0.15kg aluminum wire / shot / ton of steel for precipitation deoxidation, and add calcium oxide and 6%-10% fluorite by weight. The basicity is controlled at 5-6 to obtain a refined molten steel with the required composition and reduce the inclusions brought in by adding alloys. Not only deep deoxidation is achieved, but also the precipitation of aluminum nitride is effectively avoided, and Al2O3 inclusions are given a long enough floating time, and the inclusions are refined to meet the requirements of the molten steel for ultra-low oxygen and ultra-low sulfur.
[0046] S3, when the composition of the refined molten steel is qualified and the oxygen content is below 20ppm, a barrel insertion method is adopted to add mixed rare earth with an oxygen content of less than 1000ppm to the bottom of the ladle in batches, the amount of mixed rare earth in each batch is less than 500ppm, and the time interval for adding each batch of mixed rare earth is not less than 1 minute and not more than 3 minutes; after the mixed rare earth is added, the molten steel is isolated from air protection, the weak blowing argon pressure is 0.1-0.2MPa, the instantaneous argon flow rate is 0.5-0.6m3 / h, and the ladle is subjected to bottom blowing Ar gas weak stirring, and the weak stirring time is 10-20min. When the mixed rare earth is added, it is isolated from air protection to avoid oxidation caused by contact between rare earth and air, and to avoid the problem of unstable performance. Through the weak stirring of bottom blowing argon gas, it is ensured that the formed reactants are fully floated, and the rare earth inclusions retained in the molten steel are submicron-level, the grains are refined, and the purity of rare earth is controlled.
[0047] S4, pouring: argon protection, control the argon flow rate to 5-15m3 / h, control the oxygen concentration near the ladle nozzle to below 10ppm, the pouring flow rate to 20-60kg / s, the pouring superheat to 45-65℃; the cooling rate of the molten steel is less than 10℃ / min, and the cast ingot is obtained;
[0048] S5. Rolling: The cast steel ingot is used as raw material, and is rolled into bars with a diameter of 10-65mm through heating, rough rolling, fine rolling, cooling and finishing processes to ensure that the surface quality, dimensional accuracy and performance quality of the hot-rolled bars meet the requirements.
[0049] S6. Solution treatment: the solution temperature is 1000℃-1250℃, the holding time is 0.5-2.0h, the furnace temperature is not less than 200℃, the heating rate is 100-150℃ / h, and after solution treatment, it is cooled by water at room temperature to reduce to room temperature.
[0050] Embodiment 1:
[0051] Duplex stainless steel Example 1 was prepared according to the following method. The composition of the stainless steel in Example 1 is shown in Table 1.
[0052] Table 1. Composition formula of duplex stainless steel (wt.%)
[0053]
[0054] The preparation method of Example 1 is:
[0055] S1. Metal smelting: pure scrap steel with similar composition is added into an electric arc furnace for smelting, and the molten steel is deoxidized and deslaged to make the oxygen content 80ppm to obtain molten metal; during the molten steel smelting process, the boiling time is maintained for 30min and the weak stirring time is maintained for 20min to make the inclusions inside the molten metal float to the surface and improve the purity of the molten metal.
[0056] S2. Add alloy to the molten metal for AOD refining and LF refining. The AOD refining time is 100 min and the LF refining time is 50 min. During AOD refining, 2.3 kg of aluminum blocks are added per ton of steel for deep deoxidation, and then calcium oxide is added for desulfurization, so that the O content in the molten steel is less than 20 ppm and the S content is less than 10 ppm. During LF refining, 1 kg of aluminum powder is added to the slag surface for diffusion deoxidation, 0.12 kg of aluminum wire / shot is fed into the molten steel for precipitation deoxidation, and calcium oxide and 8% by weight of fluorite are added. The basicity is controlled to 6 to obtain a refined molten steel with components meeting the requirements.
[0057] S3. When the composition of the refined molten steel is qualified and the oxygen content is below 20ppm, a mixed rare earth with an oxygen content of 800ppm is added to the refined molten steel in batches to the bottom of the ladle by inserting a barrel. The amount of mixed rare earth in each batch is 300ppm, and the time interval for adding each batch of mixed rare earth is 2min. After the mixed rare earth is added, the molten steel is isolated from air for protection, the weak blowing argon pressure is 0.15MPa, and the instantaneous argon flow rate is 0.5m 3 / h, and the ladle is bottom-blown with Ar gas for weak stirring, and the weak stirring time is 15min.
[0058] S4, pouring: argon protection, control the argon flow rate to 5-15m 3 / h, control the oxygen concentration near the ladle nozzle below 10ppm, the pouring flow rate is 30kg / s, the pouring superheat is 50℃; the cooling rate of the molten steel is 8℃ / min, and the cast steel ingot is obtained;
[0059] S5. Rolling: The cast steel ingot is used as raw material, and is rolled into bars with a diameter of 10-65mm through heating, rough rolling, fine rolling, cooling and finishing processes to ensure that the surface quality, dimensional accuracy and performance quality of the hot-rolled bars meet the requirements.
[0060] S6. Solution treatment: the solution temperature is 1150°C, the holding time is 1h, the furnace temperature is 300°C, the heating rate is 130°C / h, and the solution is cooled with water at room temperature to obtain the finished product.
[0061] The prepared sample of Example 1 was subjected to a corrosion resistance test, and the test method was as follows:
[0062] 1) Construct a flue gas desulfurization simulation corrosion experimental device, use dead green liquid (11.4wt.% H2SO4+1.2wt.% HCl+1wt.% FeCl3+1wt.% CuCl2) to simulate the flue gas condensate, and carry out the corrosion test of Example 1 in the simulated flue gas desulfurization environment. The corrosion behavior of duplex stainless steel in the dead green liquid environment is studied by cyclic voltammetry test and scanning electron microscope observation. Cyclic voltammetry test is carried out with platinum sheet as auxiliary electrode and saturated calomel electrolysis (SCE) as reference electrode. The scanning speed of cyclic voltammetry test is 1mV / s, and the scanning potential range starts from 100mV below the open circuit potential and scans in the forward direction until the current density reaches 10mA / cm2, and then starts the reverse scanning. The scanning ends after scanning back to the starting potential (100mV below the open circuit potential). The microscopic morphology of the surface of the sample after corrosion is observed by INSPECTE SEM, and the test results are as follows: Figure 1-3 As shown, the corrosion behavior of duplex stainless steel in flue gas desulfurization environment is revealed.
[0063] Figure 1 The open circuit potential trend diagram of the artificial gap electrode of Example 1 in a 70°C dead green liquid simulation solution. Figure 1 It can be seen that the open circuit potential of the duplex stainless steel is stable at 0.45 V, the potential values are higher than 904L, and the potential trend is relatively stable. It can be seen that in this environment, the integrity of the passivation film on the surface of the duplex stainless steel of Example 1 is good and stable.
[0064] Figure 2 The cyclic voltammetry curve of the artificial gap electrode of Example 1 in a 70°C dead green liquor simulation solution. Figure 2 It can be seen that during the forward scan, the potential first passes through the open circuit potential (about 0.53 V). After that, when the potential rises from 0.53 V to 1.0 V, the electrode surface is in a passive state (the current density is 0.1 mA / cm 2 When the scanning potential is higher than 1.0V, the current density increases rapidly. When the current density reaches 10mA / cm 2The potential began to sweep back. The sweep back current density was less than the forward sweep current density, and no hysteresis loop was formed during the sweep back, indicating that the rapid increase in current density was caused by the damage of the passive film on the stainless steel surface and rapid anodic dissolution at high potential. The damaged passive film was self-repaired rapidly during the sweep back process.
[0065] Figure 3 This is the corrosion morphology after the test of Example 1. Figure 3 It can be seen that no corrosion pits occurred in Example 1, indicating that Example 1 has excellent crevice corrosion resistance.
[0066] Figure 4 Figure 1 is a cyclic voltammetry curve of duplex stainless steel Example 1 in dead green liquid at different temperatures. Figure 4 It can be seen that the back sweep current density of the cyclic voltammetry process occurring on the surface of Example 1 is smaller than the forward sweep current density, and no hysteresis loop is formed, which indicates that the local corrosion occurring on the surface of Example 1 is self-repaired.
[0067] Figure 5 Figure 1 is a corrosion morphology diagram of duplex stainless steel Example 1 after cyclic polarization test in dead green liquid at different temperatures. Figure 5 It can be seen that in the dead green solution at three temperatures, after the cyclic voltammetry test, Example 1 has no obvious pitting morphology, which indicates that Example 1 has excellent pitting corrosion resistance.
[0068] 2) A desalination simulation corrosion experimental device was constructed. A 2-fold concentrated artificial seawater electrolyte solution was prepared with analytically pure reagents and deionized water. The temperature was set to 70°C, the highest temperature in the low-temperature multi-effect seawater desalination process system. The composition of the electrolyte solution is shown in Table 2.
[0069] Table 2. Electrolyte solution composition (g / L)
[0070] Element NaCl <![CDATA[MgCl2]]> <![CDATA[NaSO4]]> <![CDATA[CaCl2]]> KCl <![CDATA[NaHCO3]]> KBr <![CDATA[H3BO3]]> <![CDATA[SrCl2]]> NaF content 49.06 10.4 8.18 2.32 1.39 0.402 0.202 0.054 0.05 0.006
[0071] The three-electrode system is composed of an electrochemical workstation, a glass electrolytic cell, a Luggin capillary and a constant temperature water bath. The working electrode is the sample of Example 1, the auxiliary electrode is a platinum electrode, and the reference electrode is a saturated calomel electrode (SCE). The working electrode is subjected to a cyclic polarization test, and the scanning speed of the cyclic polarization is 0.166mV / s. When the scanning potential reaches 400mV, the potential is retraceable; the surface SEM observation of the sample of Example 1 after the cyclic polarization test is performed; the sample of Example 1 after the cyclic polarization test is subjected to a laser confocal study to measure and count the gap depth. The test results are as follows: Figure 6-9 As shown, the crevice corrosion behavior and pitting corrosion behavior of duplex stainless steel in a simulated seawater desalination environment are revealed.
[0072] Figure 61 is a cyclic polarization curve of the gap electrode in the simulated seawater desalination environment of Example 1. Figure 6 It can be seen that the high potential local corrosion current in Example 1 is relatively small, and does not exceed 0.01A / cm 2 , indicating that the crevice corrosion rate is significantly lower. In addition, the repassivation potential is higher than the open circuit potential, indicating that once crevice corrosion occurs in the duplex stainless steel of Example 1 in the simulated seawater desalination environment, the crevice corrosion pits can be self-repaired when the potential is low.
[0073] Figure 7 This is a microscopic morphology of crevice corrosion in Example 1 in a simulated seawater desalination environment. As can be seen from the figure, a structure similar to "lace cover" still exists at the junction of the passivation zone A and the severe corrosion zone B (1), indicating that the passivation film of Example 1 has better strength and stability, better passivation properties, and low crevice corrosion sensitivity.
[0074] B(1) The grain outline can be vaguely observed in the severe corrosion zone, and there is a pitted corrosion morphology inside the grain. The grains bulge outward, and there are large gaps between the grains. The gaps are where the ferrite is dissolved first, while the pitted bulged grains are the residual austenite. This indicates that the local acidification is severe in this area, the stainless steel passivation film is basically dissolved, and a galvanic corrosion effect occurs between austenite and ferrite, with ferrite corroding first. B(2) In the general corrosion zone, the corroded residual austenite is more prominent and the corrosion morphology is more three-dimensional, while the corrosion pits here are shallow, indicating that the local acidification degree here is not enough to dissolve all the austenite. Under the galvanic effect, the ferrite corrodes deeply toward each other. B(3) The dual-phase structure of ferrite and austenite can still be clearly observed in the slight corrosion zone, and the austenite phase is slightly bulged.
[0075] The duplex stainless steel of Example 1 was subjected to cyclic voltammetry using a Pt sheet as an auxiliary electrode and saturated calomel electrolysis (SCE) as a reference electrode. The scanning speed of the cyclic voltammetry test was 1 mV / s, and the scanning potential range was forward scanned from 100 mV below the open circuit potential until the current density reached 1 mA / cm2, and then reverse scan was started. The scan was terminated after scanning back to the starting potential (100 mV below the open circuit potential). The microscopic morphology of the surface of the sample after corrosion was observed using an INSPECTE SEM. The experimental temperatures were set at 20°C, 40°C, and 70°C, respectively.
[0076] Figure 8It is the cyclic voltammetry curve of Example 1 in seawater simulation solutions at different temperatures. It can be seen that in the process of scanning from low to high potential, the potential first passes through the open circuit potential of the stainless steel in Example 1, and then the polarization current is maintained in a very small range. At this time, the surface of the stainless steel in Example 1 is in a passivation state covered by a passivation film. When the scanning potential reaches about 0.75V, the polarization current density increases rapidly. When the potential starts to scan in reverse, the reverse scanning current density is less than the forward scanning current density. This shows that the local corrosion on the surface of the stainless steel in Example 1 in the three temperatures of twice the seawater simulation solution is self-repaired.
[0077] Fig. 9 The corrosion morphology of Example 1 after cyclic voltammetry test in 20°C and 70°C and 2 times seawater simulated solution ((a)(b) 20°C; (c)(d) 70°C). It can be seen that after the cyclic voltammetry test, no pitting pits appeared on the surface of Example 1, indicating that the pitting corrosion resistance is excellent.
[0078] The effects of CaF2 content and basicity on the average diameter of inclusions were analyzed. The test results are as follows: Fig.10 As shown. Fig.10 It can be seen that as the CaF2 content in the refined slag increases from 6% to 10%, the average diameter of the inclusions decreases from 2.18μm to 1.56μm, indicating that increasing the CaF2 content is beneficial to the refinement of inclusions; in addition, when the CaF2 content is fixed at 8% and the basicity is reduced from 6 to 3.5, the average diameter of the inclusions increases from 1.56μm to 1.91μm, indicating that high basicity is beneficial to reducing the size of inclusions.
[0079] The inclusion analysis of the product of Example 1 shows that the grain size of the dual-phase steel is above level 9, the inclusions of type A are 0, and the inclusions of type B+C+D are ≤ level 1.
[0080] The physical properties of the product of Example 1 were analyzed, and the analysis results were: yield strength greater than 650 MPa, tensile strength of 900 MPa, elongation greater than 25%, cross-sectional shrinkage greater than 45%, and impact energy ≥100 J at a temperature below -46°C.
[0081] It should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. For those skilled in the art, the technical solutions described in the above embodiments can be modified, or some of the technical features therein can be replaced by equivalents; and all these modifications and replacements should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A duplex stainless steel containing rare earth elements, characterized in that: The invention comprises the following components in weight percentage: C<0.04%, Si: 0.2-0.8%, Mn: 0.8-1.5%, S≤0.005%, P≤0.02%, Cr: 22.0-27.0%, Ni: 5.0-7.0%, Mo: 3.0-4.0%, N: 0.24-0.32%, B: 0.002-0.005%, mixed rare earth: 0.05-0.10%, and the balance is iron and other inevitable impurities.
2. The duplex stainless steel containing rare earth elements according to claim 1, characterized in that: The mass percentage of cerium in the mixed rare earth is 58-65%; the mass percentage of lanthanum is 30-34%.
3. The process for preparing duplex stainless steel containing rare earth elements according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Metal smelting: pure scrap steel with similar composition is added into an electric arc furnace for smelting, and the molten steel is deoxidized and deslaged to make the oxygen content less than 100ppm to obtain molten metal; S2, adding alloy to the molten metal for AOD refining and LF refining to obtain refined molten steel; S3. When the composition of the molten steel to be refined is qualified and the oxygen content is below 20ppm, a mixed rare earth with an oxygen content of less than 1000ppm is added to the molten steel in batches to the bottom of the ladle by inserting a barrel, and the amount of the mixed rare earth in each batch is less than 500ppm, and the time interval for adding each batch of mixed rare earth is not less than 1 minute and not more than 3 minutes; S4, pouring: argon protection, control the argon flow rate to 5-15m 3 / h, control the oxygen concentration near the ladle nozzle below 10ppm, the pouring flow rate is 20-60kg / s, the pouring superheat is 45-65℃; the cooling rate of the molten steel is less than 10℃ / min, and the cast steel ingot is obtained; S5, rolling: the cast steel ingot is used as raw material, and is subjected to heating, rough rolling, finish rolling, cooling and finishing processes to be rolled into bars with a diameter of 10-65 mm; S6. Solution treatment: the solution temperature is 1000℃-1250℃, and the holding time is 0.5-2.0h.
4. The process for preparing duplex stainless steel according to claim 3, characterized in that: In step S1, during the molten steel smelting process, the boiling time is maintained at 30-50 minutes and the weak stirring time is maintained at 10-40 minutes, so that the inclusions inside the molten metal float to the surface.
5. The process for preparing duplex stainless steel according to claim 3, characterized in that: In step S2, the AOD refining time is 60-120 min, and the LF refining time is 30-60 min.
6. The process for preparing duplex stainless steel according to claim 3, characterized in that: In step S2, during AOD refining, 2.0-2.5 kg / ton of aluminum blocks are added to perform deep deoxidation of the molten steel, and then calcium oxide is added to perform S removal, so that the O content in the molten steel is less than 20 ppm and the S content is less than 10 ppm.
7. The process for preparing duplex stainless steel according to claim 3, characterized in that: In step S2, during LF refining, 0.8-1.5 kg / ton of aluminum powder is added to the slag surface for diffusion deoxidation, 0.1-0.15 kg / ton of aluminum wire / shot is fed into the molten steel for precipitation deoxidation, and calcium oxide and 6%-10% by weight of fluorite are added, and the basicity is controlled at 5-6 to obtain a refined molten steel with components meeting the requirements.
8. The process for preparing duplex stainless steel according to claim 3, characterized in that: In step S3, after the mixed rare earth is added, the molten steel is isolated from air for protection, the weak blowing argon pressure is 0.1-0.2MPa, and the instantaneous argon flow rate is 0.5-0.6m 3 / h, and the ladle is bottom-blown with Ar gas for weak stirring, and the weak stirring time is 10-20min.
9. The process for preparing duplex stainless steel according to claim 3, characterized in that: In step S6, the temperature entering the furnace is not less than 200°C, the heating rate is 100-150°C / h, and after solutionizing, it is cooled by water at room temperature to reduce to room temperature.
Citation Information
Cited By
High-purity duplex stainless steel alloy and preparation process thereof
CN122071778A